Associação da doença periodontal e o diabetes: revisão de literatura - Almeida, Gabriel Carvalho (2022)
Introduction: Periodontal disease and diabetes are chronic pathologies and have inflammation in common, where hyperglycemia can exacerbate the inflammatory state through a significant increase in the production of inflammatory cytokines in the periodontium, causing an increase in periodontal destruction, in contrast to the worsening inflammation periodontal inflammation affects glycemic control. Objectives: To demonstrate possible associations between periodontal disease and diabetes. Methodology: This is a literature review and the scientific databases consulted for the tracking of scientific studies were: Virtual Health Library (VHL), PubMed and Scientific Electronic Library Online (SciELO). The search strategy consisted of descriptors extracted from the Medical Subject Headings (MeSH): “diabetes”, “periodontal dieases” and “periodontitis”. Conclusion: The bidimensionality between diabetes and periodontal disease was observed and the relationship between diabetes and periodontal disease was concluded and, on the other hand, the exacerbation of periodontal disease increases the levels of directional serum metabolic markers by insulin resistance and periodontal consequent did not increase the HbA1c index.